Penggunaan Bahasa Jawa dalam Lirik Lagu “Lathi” dari Weird Genius - Lukman Zulfi; Hasbi Assiddiqi (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The song Lathi by Weird Genius became a global sensation due to its fusion of modern electronic music with traditional Indonesian culture. The inclusion of Javanese language in its lyrics stands out, adding emotional, spiritual, and cultural layers. This study explores the rationale behind the Javanese lyrics in Lathi, their role in enriching the song's meaning, and their influence on both local and global audience reception.This qualitative study adopts a descriptive-analytical approach, utilizing the song's lyrics, interviews with Weird Genius, and media reviews as primary data sources. Semiotic analysis reveals the symbolic significance of the Javanese lyrics. Findings indicate that these elements not only enhance Lathi's uniqueness but also emphasize Indonesia's cultural identity on the global stage. The phrase "Kowe ra iso mlayu saka kesalahan" conveys a universal moral message while showcasing local richness. The global success of Lathi highlights how integrating traditional elements into modern art can effectively appeal to international markets. This study underscores the strategic value of promoting local culture through contemporary art to sustain cultural identity amid globalization.